2006
DOI: 10.1007/s11099-006-0023-8
|View full text |Cite
|
Sign up to set email alerts
|

Variations in photosynthetic rate and associated parameters with age of oil palm leaves under irrigation

Abstract: Net photosynthetic rate (P N ), transpiration rate (E), and stomatal conductance (g s ) in an adult oil palm (Elaeis guineensis) canopy were highest in the 9 th leaf and progressively declined with leaf age. Larger leaf area (LA) and leaf dry mass (LDM) were recorded in middle leaves. P N showed a significant positive correlation with g s and a negative relationship with leaf mass per area (ALM). The oil palm leaf remains photosynthetically active for a longer time in the canopy which contributes significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 5 publications
3
9
0
1
Order By: Relevance
“…While the mid morning P N /g s was higher in September, late winter, compared to the other months, P N /C i remained at a similar level throughout the year, in accordance to the stomatal limitation discussed by Flexas et al (2001). Positive correlations between P N and g s were found also in oil palms (Smith 1989, 1993, Suresh and Nagamani 2006, and in coconut (Repellin et al 1997). Peach palms showed predawn F v /F m values around 0.8 (Fig.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…While the mid morning P N /g s was higher in September, late winter, compared to the other months, P N /C i remained at a similar level throughout the year, in accordance to the stomatal limitation discussed by Flexas et al (2001). Positive correlations between P N and g s were found also in oil palms (Smith 1989, 1993, Suresh and Nagamani 2006, and in coconut (Repellin et al 1997). Peach palms showed predawn F v /F m values around 0.8 (Fig.…”
Section: Discussionsupporting
confidence: 77%
“…In comparison with other palms of economic importance, such as coconut palm (Gomes et al 2002a, 2002b, Gomes et al 2007, Passos et al 2009) and oil palm (Corley 1983, Dufrêne and Saugier 1993, Lamade and Setiyo 1996, Suresh and Nagamani 2006, photosynthesis of the peach palm has been less studied, even under the natural Amazonian conditions. A low P N of peach palm was reported in Willis et al (1992), however neither experimental conditions, nor the ontogeny of the leaves was documented.…”
Section: Introductionmentioning
confidence: 99%
“…Further, it is also expected that palms might have not responded either to the methods or levels of irrigation imposed with particular reference to total carotenoids content. Suresh and Nagamani (2006) also reported similar kind of trend in the total carotenoids conetent of adult oil palms. Upadhyay (2016) also reported similar kind of observation in the areca nut seedlings.…”
Section: Resultssupporting
confidence: 58%
“…2 Many authors 1,35-37 have reported a decrease in the photosynthetic rate of the oil palm canopy after rank 9 but the leaves remained photosynthetically active even when located in the lower part of the canopy. 25,[35][36][37] The faster decrease in the stomatal conductance, after rank 1, than in photosynthesis, 1 could indicate a rapid control of g s by feedback of the photosynthates produced. Only a smooth peak of g s could be observed around rank 10 in relation to photosynthesis.…”
Section: C-depleted From Rank 2 To Pruningmentioning
confidence: 99%